2009
DOI: 10.4161/psb.4.8.9080
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of momilactone A and B by the mossHypnum plumaeforme

Abstract: Although rice and the moss Hypnum plumaeforme Wils are taxonomically quite distinct, momilactone A and B have so far been found only in rice and H. plumaeforme. 1-4 Momilactone A and B in rice plants are known to be synthesized as a part of defensive responses and exhibit antibacterial and antifungal activities. 5-7 Rice plants were also found to secrete momilactone A and B from their roots into the rhizosphere and exhibit alleloapthic activities against weed plants. 1,[8][9][10] The plant rhizosphere is a den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…As an allelochemical in rice and moss plants with a 19, 6 β-lactone structure [48,49], Momilactone (A and B) has been proposed as environmentally-safe fungicidal and bacteriostatic agents [50]. Previous studies on its antifungal properties against the highly destructive rice blast pathogen Piricularia oryzae [49,51], as well as an integral part of the defense system of the moss Hypnum plumaeforme [52][53][54][55], strongly support the findings of the present study. In addition, momilactones A and B significantly suppressed F. oxysporum and F. solani activities in vitro [56].…”
Section: Discussionsupporting
confidence: 89%
“…As an allelochemical in rice and moss plants with a 19, 6 β-lactone structure [48,49], Momilactone (A and B) has been proposed as environmentally-safe fungicidal and bacteriostatic agents [50]. Previous studies on its antifungal properties against the highly destructive rice blast pathogen Piricularia oryzae [49,51], as well as an integral part of the defense system of the moss Hypnum plumaeforme [52][53][54][55], strongly support the findings of the present study. In addition, momilactones A and B significantly suppressed F. oxysporum and F. solani activities in vitro [56].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, six of the proteins identified above were in the MVA pathway, but none was in the MEP pathway; therefore, replanting might promote the accumulation of terpenoids primarily via the MVA pathway. Furthermore, two unregulated proteins in replanted R. glutinosa were identified: momilactone A (MAS), which is a diterpenoid that might have been induced by a pathogen, and JA [ 48 , 49 ], which has demonstrated potential allelopathic properties in rice [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In P. patens ultraviolet (UV)-B irradiation induced genes that encode for enzymes for flavonoid biosynthesis (Wolf et al, 2010), and in the liverwort M. polymorpha, UV-C induced the synthesis of the bisbibenzyls isoriccardin C, marchantin C, and riccardin F, through the abscisic acid (ABA) signaling pathway (Kageyama et al, 2015). Production of phytoalexins momilactone A and B were also induced by UV and, jasmonic acid-and cantharidin-treatments in the moss H. plumaeforme (Kato-Noguchi, 2009). Moreover, it was shown that intracellular flavonoid level in M. linearis were induced by the application of methyl jasmonate, 2-(2-fluoro-6-nitrobenzylsulfa-nyl) pyridine-4-carbothioamide and 2,4-Dichlorophenoxyacetic acid (Krishnan and Murugan, 2014).…”
Section: B Elicitation Of Production Of Natural Products In Bryophytesmentioning
confidence: 99%